High Affinity Decynium-22 Binding to Brain Membrane Homogenates and Reduced Dorsal Camouflaging after Acute Exposure to it in Zebrafish - Gould, Georgianna G.; Barba-Escobedo, Priscilla A.; Horton, Rebecca E.; Daws, Lynette C. (Frontiers in Pharmacology, 2022)
Organic cation transporters (OCTs) are expressed in mammalian brain, kidney, liver, placenta and intestines, where they facilitate transport of cations and other substrates between extracellular fluids and cells. Despite increasing reliance on ectothermic vertebrates as alternative toxicology models, properties of their OCT homologs transporting many drugs and toxins remain poorly characterized. Recently in zebrafish (Danio rerio) two proteins with functional similarities to human OCTs were shown to be highly expressed in liver, kidney, eye and brain. This study is the first to characterize in vivo uptake to brain and high affinity brain membrane binding of the mammalian OCT blocker 1-1’-diethyl-2,2’cyanine iodide (decynium-22 or D-22), in zebrafish. Membrane saturation binding of [3H] D-22 in pooled zebrafish whole brain versus mouse hippocampal homogenates revealed a high affinity binding site with a KD of 5 ± 2.5 nM and Bmax of 1974 ± 410 fmol/mg protein in zebrafish brain, and a KD of 3.3 ± 2.3 and Bmax of 704 ± 182 fmol/mg protein in mouse hippocampus. Binding of [3H] D-22 to brain membrane homogenates was partially blocked by the neurotoxic cation 1-methyl-4-phenylpyridinium (MPP+), a known OCT substrate. To determine if bath D-22 exposures reach the brain, zebrafish were exposed to 25 nM tritiated D-22 for 10 min, and 736 ± 68 ng/g wet weight [3H] D-22 was bound. Acute behavioral effects of D-22 in zebrafish in two anxiety-relevant tests were characterized. Initially 12.5, 25 or 50 mg/L D-22 had no effect on height in the water column of a dive tank or entries and time spent in white arms of a light/dark plus maze. By contrast, 25 mg/L buspirone increased zebrafish dive tank top-dwelling (p < 0.05), an anticipated anxiolytic effect. However zebrafish treated with 50 mg/L D-22 made more white arm entries, and females spent more time in white than controls. Based on these findings it appears D-22 bath treatments reach zebrafish brain and have partial anxiolytic properties, reducing anti-predator floor camouflage behaviors, without increasing vertical exploration. High affinity binding of [3H] D-22 in zebrafish brain and mice was similar, with nanomolar affinity, possibly at conserved OCT site(s).